STRATEGI PENDIDIK DALAM MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK PADA MASA BELAJAR DARI RUMAH - Afipah Afipah; Dyah Ageng Pramesty Koenarso (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2022)
The purpose in the study was to find out the teacher's strategy in developing children's cognitive abilities during the learning period from home period in RA Islam Terpadu Ta'dIbul Amin Banjarmasin. This research use descriptive qualitative method. The object in this research is the teacher's strategy in developing children's cognitive abilities during the learning period from home, while the subject is 4 teachers. The data collection in this research use observation, interview and documentation. From the results of the research conducted, the strategy carried out by teachers in developing children's cognitive abilities is carried out with varied activities, and using media around the child. The use of media around children aims to make it easier for parents to follow the learning process flow, in the hope that learning objectives can be achieved effectively and efficiently. Keywords: Cognitive Ability, Early Childhood, Learning from home, Strategy